Accounting for Islamic finance - Abd Rahman, Abdul Razak; Yusof, Amir Alfatakh; Mohd Ariffin, Noraini; Rosman, Romzie; Abdul Ghani, Badlisyah; Abd Latiff, Radziah; Yusso, Shelia Ainon; Rajagopal, Harun Kannan; Ahmed, Mezbah Uddin; Zailani, Nurul Hidayah; Sulaiman, Maliah; Ramli, Rasmimi; et al. (Malaysian Institute of Accountants, 2020)
This book is an effort to document the application of the Malaysian Financial Reporting Standards (MFRS) on Islamic finance transactions in Islamic banking, takaful entities and Islamic asset management in Malaysia. There are 15 chapters in this book which are divided into four parts. Part I, which covers Chapters 1 to 3, provides a background on Islamic finance development in Malaysia and sets the scene to the rest of the chapters in this book. Chapter 1 discusses the differences between Islamic and conventional financial institutions which comprise banking, takaful and asset management companies. Chapter 2 explains Malaysia’s journey on Islamic banking where, among others, it entails discussion on development of regulatory requirements on Islamic finance since 1983 and using accrual accounting for Islamic finance transactions. While Chapter 3 focuses on the adoption of accounting standards by the Islamic financial institutions and its implications on Islamic finance. Parts II to IV that cover 12 chapters, discuss the application of MFRSs on assets, liabilities, income, expenses and equity of Islamic banks, takaful entities and Islamic asset management companies. The discussion on assets, liabilities and equity look at definition/nature, recognition, measurement as well as presentation and disclosure of the items in the financial statements of these entities. Parts II and III that cover Islamic banking and takaful entities respectively, also include an introduction chapter on understanding of Islamic banks’ and takaful entities’ financial statements as well as a brief discussion on future consideration of accounting standards for those entities, given the continuous development of the accounting standards affecting them. It is our hope that this book would instil the knowledge of applying MFRSs on Islamic finance transactions among the students of universities and institute of higher learning as well as provide useful reference materials in teaching the application of MFRS on Islamic finance transactions. In addition, this book could be a point of reference that explains and clarifies the rationale behind current applications of MFRS for Islamic finance either for Islamic financial institutions or other industries.